Perceived Organizational Support and Turnover Intention: Mediating Effects of Satisfaction and Stress of Palm Oil Harvester - Aulia, Aulia; Putra, Dimas Brian Adi; Amalia, Frida; Alpradisa, Hafiz; Purnamasari, Alfi (Journal of Educational, Health and Community Psychology, 2025)
Turnover is a persistent issue within organizations. Its impact can have both direct and indirect effects on the company. A high rate of turnover intention can lead to instability in the organizational structure, which may subsequently decrease the effectiveness and efficiency of the company’s operations. This study examines the roles of job satisfaction and job stress in mediating the relationship between perceived organizational support and turnover intention. The research employs a quantitative approach using a cross-sectional study design. The characteristic population for this study consists of oil palm harvester employees at PT XY, and a saturated sampling technique was utilized, resulting in a total sample of 145 oil palm harvesters. The instruments employed in the study include the perceived organizational support scale, job satisfaction scale, job stress scale, and turnover intention scale. The findings indicate that job stress partially mediates the relationship between perceived organizational support and turnover intention (β=-0.348, p<0.01) among harvesting employees. Meanwhile, job satisfaction does not mediate this relationship (β=-0.058, p>0.01) for the harvester employees at PT XY. These findings provide practical insights for human resource strategies aimed at reducing employee turnover, particularly in labor-intensive plantation sectors.